Mashlahah Mursalah dalam Aktifitas Ekonomi dan Bisnis Islam - M. Zikwan; Erwin Azhari (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The purpose of this research is to provide an overview of maslahah in Islamic economics and business. Sharia economics and business have become highly popular terms among the global community today. These terms not only reflect the existence of business theories from a Sharia perspective ontologically but also indicate the presence of epistemological and axiological aspects. Generally, business is an activity carried out by humans with the aim of generating income to meet the needs and desires of life by effectively and efficiently managing economic resources. In Islam, business comprises a series of activities encompassing various types, without limitation on the amount of wealth ownership and profit. However, business in Islam is restricted in the acquisition and use of wealth, with rules regarding what is halal (permissible) and haram (forbidden). This research employs a literature review approach. The findings of this study indicate that maslahah in Islamic economics is highly necessary for the current era, as economic cases will continue to increase and emerge, thereby automatically requiring evidence to determine their legality which may not be clearly explained in either the Qur'an or Hadith. Maslahah in Islamic business is highly essential because it serves as an analytical tool for Islamic legal scholars, who are expected to discover new laws to address these issues so that the concept of Sharia economics and business is truly accepted and meets the needs of society.